2022
DOI: 10.1007/s00167-022-07068-2
|View full text |Cite
|
Sign up to set email alerts
|

Medial meniscus tears are most prevalent in type I ACL tears, while type I ACL tears only account for 8% of all ACL tears

Abstract: Purpose This study aimed to assess the distribution of diferent anterior cruciate ligament (ACL) tear locations in diferent magnetic resonance imaging (MRI) planes, and to explore the relationships of ACL tear types with both meniscus injuries and bone bruising. Methods A retrospective study was performed in patients under 60 years old who underwent MRI scans in the sagittal and coronal oblique planes of the knee for ACL tears between 2014 and 2020. Patients with reports of chronic tears, partial tears, or pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…This finding may imply that there is a relationship between the intensity of the initial trauma, the degree of ACL damage, delay to surgery, as it has been found to be a risk factor for smaller remnant volume, and the ramp lesion. Recently, Tan et al [36] found an association between the type of ACL injury and the prevalence of medial meniscus tear.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may imply that there is a relationship between the intensity of the initial trauma, the degree of ACL damage, delay to surgery, as it has been found to be a risk factor for smaller remnant volume, and the ramp lesion. Recently, Tan et al [36] found an association between the type of ACL injury and the prevalence of medial meniscus tear.…”
Section: Discussionmentioning
confidence: 99%
“…Heat therapy is a safe and effective treatment option for the majority of aches and pains. 13 When treating a new wound, keep all sources of heat away from it. This method may result in greater subcutaneous bleeding, making treatment of the underlying disease more challenging.…”
Section: Introductionmentioning
confidence: 99%